Effect of Operating Variables and Kinetics of the Lipase Catalyzed Transesterification of Ethylene Carbonate and Glycerol - Ana Gutierrez-Lazaro; Daniel Velasco; Diego E. Boldrini; Pedro Yustos; Jesus Esteban; Miguel Ladero (Fermentation, 2018)
Glycerol carbonate (GC) is a value-added product originating from the valorization of widely available glycerol (Gly), a side stream from the production of biodiesel. Here we approach the production of this chemical comparing two reactions based on the transesterification of Gly with dimethyl carbonate (DMC) and ethylene carbonate (EC). When using DMC, it was observed that the free enzyme CALB (lipase B from Candida antarctica) gave the best results, whereas Eversa Transform (a genetic modification of Thermomyces lanuginosus lipase) performed better than the rest if EC was the reagent. With the selected catalysts, their immobilized analogous enzymes Novozym 435 and Lypozyme TL IM, respectively, were also tested. Observing that the yields for the reaction with EC were significantly faster, other operating variables were evaluated, resulting the best performance using a closed system, tert-butanol as solvent, a concentration of enzyme Eversa Transform of 3% w/w, a molar excess of EC:Gly of 9:1 and a temperature of 60 °C. Finally, several runs were conducted at different temperatures and molar ratios of EC:Gly, fitting a kinetic model to all experimental data for the reaction catalyzed with Eversa Transform. This model included the bimolecular transesterification reaction of Gly and EC catalyzed by the lipase and a reversible ring-opening polymerization of EC.